Analysis of Teacher’s Professionalism in Implementing the Merdeka Curriculum Program at SD Negeri 3 Lembak (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
A Merdeka curriculum is a curriculum that demands effectiveness in the learning process. For this reason, teachers must have high professionalism to implement a Merdeka curriculum in the learning process. This research aims to describe teacher’s professionalism in the learning process. This type of research is descriptive qualitative research. Data collection tools use documentation, interviews, observation, and literature review. The data analysis technique uses qualitative descriptive analysis techniques. The results of the research state that SD Negeri 3 Lembak teachers can implement the Merdeka curriculum well through planning, implementing, and evaluating learning based on the Independent Curriculum. The obstacles faced by teachers include limited school resources, teacher skills, adaptation, and diverse needs, interests, and learning styles. Solutions taken to overcome obstacles include training and professional development for teachers, collaboration between teachers, coaching and mentoring through a strong leadership role to support implementing the Independent Learning Curriculum.